Environmental Challenges Facing a Growing City: Sunyani Case Study - Anane, Edward Twum (Consilience, 2013)
This photo essay illustrates the environmental challenges facing a rapidly growing urban settlement in Ghana. Sunyani is one of the fastest growing cities in Ghana. The population of the city increased from 38,634 in March 1984 to 61,992 in March 2000 (Ghana Statistical Service, 2002). This trend presents serious development challenges to the city as high rates of population growth are not matched with increased provision of social services and infrastructure. The city authorities will have to adopt appropriate urban planning strategies if the city is to develop sustainably.